2017
DOI: 10.1186/s12931-017-0550-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-term exposure to PM2.5 and vanadium and changes in asthma gene DNA methylation and lung function decrements among urban children

Abstract: BackgroundBoth short and long-term exposure to traffic-related air pollutants have been associated with asthma and reduced lung function. We hypothesized that short-term indoor exposure to fine particulate matter <2.5 μm (PM2.5) and vanadium (V) would be associated with altered buccal cell DNA methylation of targeted asthma genes and decreased lung function among urban children in a nested subcohort of African American and Dominican children.MethodsSix day integrated levels of air pollutants were measured from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 67 publications
(81 reference statements)
0
46
0
Order By: Relevance
“…Exposure to PM 2.5 is associated with oxidative stress and impaired lung function. 54 , 55 , 56 A burst of reactive oxygen species induced by PM 2.5 was found in the neutrophils of asthmatic patients. 57 Deng et al 58 reported that PM 2.5 induces oxidative stress by increasing the expression of glutamate-cysteine ligase catalytic subunit (GCLC), heme oxygenase-1 (HO-1), and NADPH quinone oxidoreductase (NQO-1)in human lung epithelial cells (A549), and thereby activates Nrf2 in the phosphatidylinositol-4,5-bisphosphate 3-kinase (PIK3)/AKT signaling pathway.…”
Section: Effects Of Pm On Allergic Respiratory Diseasesmentioning
confidence: 93%
“…Exposure to PM 2.5 is associated with oxidative stress and impaired lung function. 54 , 55 , 56 A burst of reactive oxygen species induced by PM 2.5 was found in the neutrophils of asthmatic patients. 57 Deng et al 58 reported that PM 2.5 induces oxidative stress by increasing the expression of glutamate-cysteine ligase catalytic subunit (GCLC), heme oxygenase-1 (HO-1), and NADPH quinone oxidoreductase (NQO-1)in human lung epithelial cells (A549), and thereby activates Nrf2 in the phosphatidylinositol-4,5-bisphosphate 3-kinase (PIK3)/AKT signaling pathway.…”
Section: Effects Of Pm On Allergic Respiratory Diseasesmentioning
confidence: 93%
“…Hypermethylation of CpG islands in Foxp3 associated with chronic exposure to DEP leads to the suppression of Treg function and increased asthma severity as assessed by symptoms and lung function [77]. In addition, vanadium (a component of ROFA) was associated with altered DNA methylation of allergic and proinflammatory asthma genes implicated in air-pollution-related asthma [78]. Recently, authors have demonstrated that health effects of acute particulate exposure on asthma were associated with changes in cysteinyl leukotriene (CysLTR 1 ) expression and methylation of CpG sites on CysLTR 1 and leukotriene C4 synthase genes [79].…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Another investigation conducted in New York City, NY, USA, showed how exposure to vanadium (considered as a trace metal component of PM), but not to PM 2.5 , was associated with lower DNA methylation of IL-4 (− 0.80, 95% Cl 0.65–0.98, p < 0.05) and IFN-γ (− 0.81, Cl 0.67–0.98); 6-day integrated levels of air pollutants were measured from homes of 163 children (ages 9–14), and repeated 6 months later [26]. The same authors determined also the effects of black carbon (BC) exposure on DNA methylation of pro-inflammatory genes linked to airway inflammation in asthmatic subjects.…”
Section: Childhoodmentioning
confidence: 99%